2016
DOI: 10.1039/c5tc04005a
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free relaxor ferroelectric ceramics with high optical transparency and energy storage ability

Abstract: We prepared highly transparent relaxor ferroelectric ceramics based on (K0.5Na0.5)NbO3 using a pressure-less solid-state sintering method without using hot isostatic pressing and spark plasma sintering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(147 citation statements)
references
References 43 publications
3
142
2
Order By: Relevance
“…At higher values of x , the ceramics continually display reduced grain size to approximately 0.2 μm. Similar results were also reported in a series of A(B'B”)O 3 ‐modifed KNN ceramics . Although several explanations have been proposed, the origin of such submicron‐grains in A(B'B”)O 3 ‐modified KNN ceramics is still unclear.…”
Section: Resultssupporting
confidence: 84%
“…At higher values of x , the ceramics continually display reduced grain size to approximately 0.2 μm. Similar results were also reported in a series of A(B'B”)O 3 ‐modifed KNN ceramics . Although several explanations have been proposed, the origin of such submicron‐grains in A(B'B”)O 3 ‐modified KNN ceramics is still unclear.…”
Section: Resultssupporting
confidence: 84%
“…The recoverable energy storage efficiency η is equal to the ratio of W rec to W total . The energy loss density W loss and the recoverable energy storage efficiency η are calculated by using the following equations:Wnormaltotal=Wnormalrec+Wnormalloss…”
Section: Resultsmentioning
confidence: 99%
“…However, almost all the KNN‐based ferroelectric ceramics examined in previous studies do not satisfy the requirement of both high optical transmittance and high energy storage density. Tables and show the visible optical transparency and energy storage density of most KNN‐based ceramics studied during the 2014‐2017 time period . It was found that transparent ferroelectric ceramics with high energy storage densities have rarely been created in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the demands for electrical energy‐storage capacitors in the field of pulsed power applications and the increasing demands of society, dielectric capacitors for high energy‐storage density devices have been widely investigated and have played a vital role, especially in ceramic capacitors . In comparison to batteries and other energy‐storage devices, ceramic capacitors possess a faster charge–discharge rate and superior mechanical and thermal properties . Thus, ceramic dielectric materials are considered to be the best potential candidates for pulsed capacitor applications.…”
Section: Introductionmentioning
confidence: 99%